The Classification of Majhūl Narrators and Its Effect on the Acceptance of Hadith (Islamic Sciences Journal, 2025)
ABSTRACTPraise be to Allah, Lord of the Worlds, and may peace and blessings be upon the Messenger of Allah, his family, and companions. The acceptance of narrators’ reports is a central concern in the science of hadith. Due to natural differences in memory, comprehension, and accuracy, narrators vary in reliability. Moreover, ignorance and lack of recognition are unavoidable human limitations. This study examines the classification of al-majhūlūn (unknown narrators), whose status differs across hadith scholars. While some are judged trustworthy through sound evaluation, others remain unknown due to methodological differences, scholarly temperament, or simple oversight. In some cases, narrators are prematurely deemed “unknown” despite their  authentication by leading authorities.By surveying the opinions of hadith critics, the study identifies seven categories of unknown narrators. These categories are arranged in descending order, from the strongest level of acceptability to the weakest, based on criteria established by expert scholarship. Such a framework enables more precise judgments regarding narration authenticity.The study aims to increase awareness among students of hadith about the complexity of the “unknown” label, warning against hasty dismissal of narrators and encouraging a careful, evidence-based approach in assessing reports.
Keywords: Ranks, Unknown narrators, Acceptance, Impact, Narratio